1995
DOI: 10.1148/radiology.196.3.7644639
|View full text |Cite
|
Sign up to set email alerts
|

Suture closure in the human chondrocranium: CT assessment.

Abstract: The complex process of skull base development is chronicled, which provides CT standards for judgment of the patterns and timing of sutural or synchondrosal closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
129
2
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 0 publications
7
129
2
10
Order By: Relevance
“…Complex developmental patterns in this site may result in several residual linear defects Review of the embryology of the occipital bone shows that six ossification centers are present 1,3,5) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Complex developmental patterns in this site may result in several residual linear defects Review of the embryology of the occipital bone shows that six ossification centers are present 1,3,5) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Melsen [4] reported that closure had taken place in the interval between eruption of the second and third molars. Computed tomography of the spheno-occipital synchondrosis showed signs of early fusion by age 8 years of age; the age of closure was 16 years in girls and 18 years in boys [72]. On the other hand, in postmortem histologic and micro-radiographic studies of the sphenooccipital synchondrosis, Ingervall and Thilander observed closure as the appearance of bony bridges and demonstrated that the average age of closure in females is around 14 years and that the spheno-occipital synchondrosis is never completely open in many girls older than 13 years and 9 months; the corresponding age for the boys is 16 years [3,21].…”
Section: Time Of Closure Of the Spheno-occipital Synchondrosismentioning
confidence: 98%
“…Patency of these sutures could lead to spread of air and hyperpneumatisation. (7,30) Patients with hyerpneumatised skull base and temporal bone would be more prone to develop spontaneous pneumocephalus with sudden change in pressure gradient.…”
Section: Mechanismmentioning
confidence: 99%